Acquired hemophilia A in a woman with systemic lupus erythematosus: A case report and review of literature. Issue 43 (23rd October 2020) - Shen, Pan; Li, Jing; Tu, Shenghao; Chen, Gang; Chen, Chao
Abstract: Rationale: Acquired hemophilia A (AHA) is a rare autoimmune disease caused by autoantibodies directed against the activity of factor VIII (FVIII) and presents with prolonged bleeding. 5.7% of systemic lupus erythematosus (SLE) patients are affected by AHA. Patient concerns: A 51-year-old female patient with SLE presenting with the fatigue and spontaneous clinical bleeding symptoms such as hematuria and ecchymoses for 1 week. Diagnosis: Laboratory examinations revealed prolongation of the activated partial thromboplastin time (APTT) (65.7 s), decreased FVIII activity (1.4%), and a titer of FVIII inhibitors of 8.5 Bethesda units/mL. Interventions: Transfusion of recombinant human FVIII (ADVATE) in combination with intravenous methylprednisolone, cyclophosphamide, plasmapheresis, and fresh frozen plasma successfully stopped the bleeding and reduced the level of FVIII inhibitor. Outcomes: The size of the hematoma slowly decreased. The skin ecchymosis was gradually absorbed, the hemoglobin count increased, and the coagulation index gradually improved. There was no new bleeding or bleeding site. The patient was discharged and transferred to a local hospital for hospice care. Lessons: AHA in a patient with SLE is rare. Once it occurs, it can be life-threatening. Clinicians should remain aware that because some cases of AHA may have features of SLE, appropriate distinction and diagnosis of these different but associated diseases is necessary.